Impaired insulin/IGF-1 is responsible for diabetic gastroparesis by damaging myenteric cholinergic neurones and interstitial cells of Cajal. Issue 5 (27th October 2017) - Yang, Shu; Wu, Bo; Sun, Haimei; Sun, Tingyi; Han, Kai; Li, Dandan; Ji, Fengqing; Zhang, Guoquan; Zhou, Deshan
Abstract : Diabetic gastroparesis is a common complication of diabetes mellitus (DM) that is characterized by decreased serum insulin and insulin-like growth factor-1 (IGF-1). Despite the fact that insulin treatment not glycemic control potently accelerated gastric emptying in type 1 DM patients, the role of insulin/InsR and IGF-1/IGF-1R signaling in diabetic gastroparesis remains incompletely elucidated. In the present study, type 1 DM mice were established and treated with insulin or Voglibose for 8 weeks. The gastric emptying was delayed from DM week 4 when the gastric InsR and IGF-1R were declined. Meanwhile, the gastric choline acetyltransferase (ChAT) was significantly reduced and the myenteric cholinergic neurones and their fibers were significantly diminished. The production of stem cell factor (SCF) was dramatically repressed in the gastric smooth muscles in DM week 6. TWereafter, interstitial cells of Cajal (ICC) were clearly lost and their networks were impaired in DM week 8. Significantly, compared with Voglibose, an 8-week treatment with insulin more efficiently delayed diabetic gastroparesis development by protecting the myenteric cholinergic neurones and ICC. In conclusion, diabetic gastroparesis was an aggressive process due to the successive damages of myenteric cholinergic neurones and ICC by impairing the insulin/InsR and IGF-1/IGF-1R signaling. Insulin therapy in the early stage may delay diabetic gastroparesis.